Assessment of Cardiovascular Functioning Among Regular Kratom (Mitragyna speciosa Korth) Users: A Case Series - Leong Bin Abdullah, Mohammad Farris Iman; Singh, Darshan (Frontiers in Pharmacology, 2021)
Multiorgan toxicities have been extensively reported in kratom (Mitragyna speciosa Korth) users in Western countries but not in Southeast Asia. Existing literature argued that this discrepancy may be due to underreporting of kratom-related toxicity cases in Southeast Asia. Hence, this case series filled the research gap by clinically assessing the cardiovascular functioning and serum mitragynine level of regular kratom users in its traditional settings in Malaysia. Nine regular kratom users without history of polysubstance use were recruited from the same community via snowball sampling and were subjected to electrocardiogram (ECG) and echocardiogram assessments. Serum mitragynine analysis was also performed by solid-phase extraction and liquid chromatography-tandem mass spectrometry. The mean serum mitragynine level was 10.3 mg/L (SD = 6.9) and ranged from 2.5 mg/L to 22.4 mg/L. Those who consumed an average daily quantity of four or more glasses of brewed kratom juice (p = 0.045) and those who had prolonged QTc intervals (p = 0.017) had significantly higher serum mitragynine level. Echocardiographic findings of all the respondents were normal except one reported left ventricular hypertrophy and another had trivial tricuspid regurgitation with pulmonary artery systolic pressure (PASP) of 10 + 5 mmHg. Regular kratom use without concomitant use of other illicit substances may not provoke any risk of cardiovascular impairment or toxicity except for prolonged QTc interval, which appeared to be dose dependent. However, as this study was limited by a small sample size, future studies with larger sample size are warranted to confirm our findings.